(3TQM GdUOQ aj Yde GdcdGe hGdJUhas - (3CMeO GdEdgjs
(3ChdgG (B:s
(3GdMeO ddg GdPi ChbafG Ydi ehGba Yde GdJhMjO hTQM UOQfG HfhQ GdESdGe hajV GdcdGe dGOGA eQGSe GdJaQjO s
(3BNQgG (B:s
(3hGdMeO ddg WdhY GdNGabjf hGdUdGI hGdSdGe Ydi SjO GdKbdjf hJMjI Gddg JYGdi Ydi LejY CMHGA Gddg ai GdOGQjf s
(3YqQa CQHQj eagQS TSJQHJi GdeDda HCMeO GdZdgi GdCKQi GdCfUGQi J (B900 (3g`s
(3JHUQI GdYfhGf (B:s
(3TQM s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs